STRATEGI TRANSFORMASI DIGITAL BARANTIN MENUJU LEMBAGA KARANTINA BERKELAS DUNIA - Erna Dwi Hartati (Journal of Innovation Research and Knowledge, 2025)
Indonesia Quarantine Agency plays a vital role in safeguarding national biosecurity, yet it still faces significant challenges in infrastructure, human resources, technology, and regulatory alignment. This study aims to formulate appropriate policy strategies to transform Barantin into a world-class quarantine institution by 2045. A qualitative-descriptive method is employed through literature review and policy analysis using the policy cycle and SWOT approach. Findings show that institutional reform must prioritize digital transformation via IQFAST 2.0 system development, modernization of OIE/IPPC-certified laboratories, and establishment of a National Biosecurity Command Center. This policy alternative is considered the most effective and has long-term impacts on improving surveillance capacity, transparency, and trade partner trust. In conclusion, digital and infrastructure transformation is the key to achieving a world-class quarantine agency to support Indonesia’s Golden Vision 2045